ANALISIS KANVAS MODEL BISNIS UNIT USAHA BUMDES NGORAN, BLITAR, JAWA TIMUR - Muizu, Wa Ode Zusnita; Prasetyo, Andreas Recki (Gapenas Publisher, 2025)
The case study was conducted at BUMDes Karya Mandiri located in Ngoran Village, Nglegok District, Blitar Regency, East Java on July 12 - 16, 2023. The main objective of this activity is that BUMDes Karya Mandiri is currently facing difficulties in mapping the business processes that are currently running and organized traditionally. Assistance and training were conducted to optimize the role of BUMDes Karya Mandiri in the multipurpose building rental business unit. Participants in this training and mentoring are the Village Head, Village Apparatus, BUMDes Management, Kelompok Sadar Wisata (Pokdarwis), MSME activists, and local residents. The Business Canvas model was used to map the business flow, identify weaknesses, and provide recommendations for development strategies. The proposed strategies, including marketing expansion, strengthening partnerships, improving venue quality and maintaining cleanliness, innovating services offered, customer loyalty programs, and cost efficiency, can serve as guidelines for BUMDes Karya Mandiri in facing market changes and improving competitiveness